Sosialisasi Media Pembelajaran Interaktif Terintegrasi Kearifan Lokal Untuk Guru SD Muhammadiyah 1 Babat - Khasanah, Linaria Arofatul Ilmi Uswatun; Kharisma, Ahmad Ipmawan; Hidayah, Rohmatul; Fitria, Natasya Ayu (Universitas Mataram, 2024)
One use of technology in learning is as a learning medium, such as interactive learning media integrated with local wisdom. Elementary school students' disinformation about understanding local culture, amidst the multicultural conditions of Indonesian society, is caused by students' low cultural literacy skills and the lack of insight provided by teachers in introducing local culture to students. Globalization will have a negative impact if we are not selective in filtering incoming foreign culture. In fact, the development of information technology in the millennial era makes it easier for students to access information easily. Conservation efforts will be more effective if started from elementary school age, therefore it is necessary to instill the values ​​of local Lamongan cultural wisdom into learning through interactive multimedia. This is illustrated in one of the elementary schools, namely SD Muhammadiyah 1 Babat, based on the results of observations, it is stated that teachers need a lot of training in the use of interactive media which teachers can utilize and use in learning so that students become more motivated in learning. For this reason, this socialization activity is a very appropriate forum for providing training in actualizing teachers' needs in improving the quality of learning through technology integrated in local wisdom-based learning content. This training provides new references in the world of education, it is hoped that teachers will be able to adapt and transform themselves both in terms of teaching and the use of teaching supporting media from conventionalization to digitalization.